IMPLEMENTASI PENDIDIKAN KARAKTER SISWA KELAS V SDN I KAUBULA - Fajrianti; Kaif, Sitti Hermayanti (Institut Daarul Qur'an Jakarta, Indonesia, 2024)
This study aims to explore the implementation of character education in fifth-grade elementary school students, focusing on six main characters: religious, disciplined, honest, responsible, independent, and tolerant. A qualitative approach with a case study design was used to gain an in-depth understanding of character education implementation. Data were collected through participatory observation, in-depth interviews, and document analysis at Kaubula State Elementary School 1. The results showed that character education was effectively integrated into various learning activities and daily life at school. Religious character was instilled through joint prayers and celebrations of religious holidays, although the diversity of students' religions posed a challenge addressed with an inclusive approach. Discipline was enforced through strict yet fair classroom rules, with necessary support from parents. Honesty was enhanced through concrete examples and rewards for honest behavior, although negative influences from outside the school needed to be anticipated. Responsible character was developed through individual and group tasks, while independence was encouraged by providing students with opportunities to make their own decisions. Tolerance was fostered through cooperative activities and discussions that respected differences, although stereotypes and prejudices remained challenges. Overall, character education in fifth grade had a positive impact on students' development, helping them become more religious, disciplined, honest, responsible, independent, and tolerant individuals. The successful implementation of character education requires continuous support from all parties, including schools, teachers, parents, and the surrounding environment. A synergistic effort among various educational components is essential to ensure that character values are deeply ingrained in students, equipping them with a strong moral foundation to face future life challenges.